2017
DOI: 10.1002/2016ja023465
|View full text |Cite
|
Sign up to set email alerts
|

Broadband high‐frequency waves detected at dipolarization fronts

Abstract: Dipolarization front (DF) is a sharp boundary most probably separating the reconnection jet from the background plasma sheet. So far at this boundary, the observed waves are mainly in low‐frequency range (e.g., magnetosonic waves and lower hybrid waves). Few high‐frequency waves are observed in this region. In this paper, we report the broadband high‐frequency wave emissions at the DF. These waves, having frequencies extending from the electron cyclotron frequency fce, up to the electron plasma frequency fpe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 50 publications
(69 reference statements)
2
57
0
Order By: Relevance
“…Reconnection jet dynamics is closely related to their interaction with the ambient plasmas. Such interaction leads to formation of particle beams (Aunai et al, ; Eastwood et al, ; Wygant et al, ), rearrangement of the local current system (Lu, Artemyev, et al, ), and various types of kinetic‐scale instabilities developing inside the jets, such as anisotropy instability (Fu et al, ; Huang et al, ; Khotyaintsev et al, ; Liu et al, ), streaming instability (Deng et al, ; Hwang et al, ; Yang et al, ), kinetic ballooning or interchange instability (Nakamura et al, ; Pritchett et al, ; Pritchett & Lu, ), and lower hybrid drift instability at the jet front (JF)/dipolarization front (Divin et al, ; Khotyaintsev et al, ; Liu et al, ; Liu et al, ; Pan et al, ). These instabilities can generate strong electrostatic/electromagnetic waves that may interact with the local plasmas, leading to energy dissipation and particle heating (Khotyaintsev et al, , ; Huang et al, ; Huang et al, ; Fu et al, ; Liu et al, , Liu et al, ; Yao et al, ; Chen, Fu, Zhang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Reconnection jet dynamics is closely related to their interaction with the ambient plasmas. Such interaction leads to formation of particle beams (Aunai et al, ; Eastwood et al, ; Wygant et al, ), rearrangement of the local current system (Lu, Artemyev, et al, ), and various types of kinetic‐scale instabilities developing inside the jets, such as anisotropy instability (Fu et al, ; Huang et al, ; Khotyaintsev et al, ; Liu et al, ), streaming instability (Deng et al, ; Hwang et al, ; Yang et al, ), kinetic ballooning or interchange instability (Nakamura et al, ; Pritchett et al, ; Pritchett & Lu, ), and lower hybrid drift instability at the jet front (JF)/dipolarization front (Divin et al, ; Khotyaintsev et al, ; Liu et al, ; Liu et al, ; Pan et al, ). These instabilities can generate strong electrostatic/electromagnetic waves that may interact with the local plasmas, leading to energy dissipation and particle heating (Khotyaintsev et al, , ; Huang et al, ; Huang et al, ; Fu et al, ; Liu et al, , Liu et al, ; Yao et al, ; Chen, Fu, Zhang, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…So far, there have been several types of electron PAD reported behind DFs. For instance, the pancake distribution (showing electron pitch angles primarily at 90°) has been observed inside growing FPRs (Fu et al, ; Liu, Fu, Cao, et al, ) or near the neutral sheet (Birn et al, ; Runov et al, ); the cigar distribution (showing electron pitch angles primarily at 0° and 180°) has been observed inside decaying FPRs (Fu et al, ; Liu, Fu, Xu, Cao, & Liu, ) or away from the neutral sheet (Birn et al, ; Runov et al, ); the isotropic distribution (showing electron pitch angles uniformly from 0° to 180°) has been observed inside steady FPRs (Fu, Khotyaintsev, Vaivads, André, Sergeev, et al, ) or associated with strong wave emissions (Deng et al, ; Fu et al, ; Huang et al, ; Hwang et al, ; Yang et al, ); the butterfly distribution (showing electron pitch angles primarily at 45° and 135°) has been observed inside expanding flux tubes behind the DFs (Liu, Fu, Cao, et al, ). These four types of electron PAD have been well discussed in previous literatures.…”
Section: Introductionmentioning
confidence: 99%
“…have investigated the electromagnetic energy conversion at the DFs by case and statistical studies and found that the energy of the fields can be significantly transferred to the plasmas and suggested that lower hybrid frequency wave activities play an important role in the energy dissipation. Zhou et al, 2014), and broadband high-frequency waves (e.g., Yang et al, 2017). Anisotropic electron distribution and gradients in magnetic field and plasma density would result in abundant waves, such as whistler waves (e.g., Deng et al, 2010;Huang et al, 2012Huang et al, , 2016Fu et al, 2014;Li et al, 2015), lower hybrid waves (e.g.…”
Section: Introductionmentioning
confidence: 99%